Effect of intraoperative intravenous lidocaine on pain and plasma interleukin-6 in patients undergoing hysterectomy - Oliveira,Caio Marcio Barros de (2015)
BACKGROUND AND OBJECTIVES: Interleukin-6 is a predictor of trauma severity. The purpose of this study was to evaluate the effect of intravenous lidocaine on pain severity and plasma interleukin-6 after hysterectomy. METHOD: A prospective, randomized, comparative, double-blind study with 40 patients, aged 18-60 years. G1 received lidocaine (2 mg kg-1 h-1) or G2 received 0.9% saline solution during the operation. Anesthesia was induced with O2/isoflurane. Pain severity (T0: awake and 6, 12, 18 and 24 h), first analgesic request, and dose of morphine in 24 h were evaluated. Interleukin-6 was measured before starting surgery (T0), 5 h after the start (T5), and 24 h after the end of surgery (T24). RESULTS: There was no difference in pain severity between groups. There was a decrease in pain severity between T0 and other measurement times in G1. Time to first supplementation was greater in G2 (76.0 ± 104.4 min) than in G1 (26.7 ± 23.3 min). There was no difference in supplemental dose of morphine between G1 (23.5 ± 12.6 mg) and G2 (18.7 ± 11.3 mg). There were increased concentrations of IL-6 in both groups from T0 to T5 and T24. There was no difference in IL-6 dosage between groups. Lidocaine concentration was 856.5 ± 364.1 ng mL-1 in T5 and 30.1 ± 14.2 ng mL-1 in T24. CONCLUSION: Intravenous lidocaine (2 mg kg-1 h-1) did not reduce pain severity and plasma levels of IL-6 in patients undergoing abdominal hysterectomy.